Performance Evaluation of Novel Micro-textured Tools in Improving the Machinability of Aluminum Alloy (Al 6063). (2016) - Rathod, Pankaj; Aravindan, S.; Venkateswara Rao P.,
Abstract: Ordered array of dots or grooves induces special functionality to the surface. Two types of textures viz. linear (perpendicular to the chip flow direction) and square were developed on plain WC inserts using focused ion beam machining. The inserts were coated with MoS2 solid lubricants using pulsed DC magnetron sputtering. Dry turning tests were carried out on aluminum alloy (Al 6063) work material. Textured tools are found to be more effective in reducing the cutting forces and sticking behaviour of the work material as compared to the non-textured tools. The novel square textured tools performed better than the linear textured tools in terms of reduced cutting forces and improved surface finish. A reduction of about 30% in cutting forces was observed with square textured tools and that with the linear textured tools was about 20% as compared to the non-textured tools. The reduction in cutting forces and the associated change in sticking behaviour are attributed to the reduction in tool-chip contact area and reduced friction at the tool-chip interface owing to the improved lubrication provided by the interlayer of solid lubricant. Textures are functioning as reservoirs of the solid lubricant which in turn reduces the friction at the chip-tool interface.